Multiple origins of kdr-type resistance in the house fly, Musca domestica. - Frank D Rinkevich; Shannon M Hedtke; Cheryl A Leichter; Sarah A Harris; Cathy Su; Seán G Brady; Vatan Taskin; Xinghui Qiu; Jeffrey G Scott (PLoS ONE, 2012)
Insecticide resistance is a model phenotype that can be used to investigate evolutionary processes underlying the spread of alleles across a global landscape, while offering valuable insights into solving the problems that resistant pests present to human health and agriculture. Pyrethroids are one of the most widely used classes of insecticides world-wide and they exert their toxic effects through interactions with the voltage-sensitive sodium channel (Vssc). Specific mutations in Vssc (kdr, kdr-his and super-kdr) are known to cause resistance to pyrethroid insecticides in house flies. In order to determine the number of evolutionary origins of kdr, kdr-his and super-kdr, we sequenced a region of Vssc from house flies collected in the USA, Turkey and China. Our phylogenetic analysis of Vssc unequivocally supports the hypothesis of multiple independent origins of kdr, super-kdr and kdr-his on an unprecedented geographic scale. The implications of these evolutionary processes on pest management are discussed.